2019
DOI: 10.1080/17515831.2019.1648066
|View full text |Cite
|
Sign up to set email alerts
|

Tribological characteristic evaluation of coconut oil dispersed with surfactant modified ceria-zirconia hybrid nanoparticles

Abstract: The tribological characteristics of coconut oil added with ceria-zirconia hybrid (Ce-Zr) nanoparticle additives are investigated using a sophisticated pin-on-disk tribometer. A chemical processing technique namely, precipitation method (PM) is used for the synthesis of Ce-Zr nanoparticles. High-end characterization practices using microscopy and spectroscopy analyses were utilized to determine their morphology, composition, and structure. A model was developed through the Response Surface Methodology (RSM) tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Finally, Danish et al [46] performed milling experiments on Inconel 718 with a sunflower oil reinforced with graphene which reduced surface roughness by 49% and tool wear by 20%. Coconut oil, one of the vegetable lubricants with the highest number of studies in the literature has been reinforced with NPs such as CeO2, Cu, CuO, MoS2, SiO2 and MWNTs [10, 23,36,47,[49][50][51] with COF and wear reductions of up to ~93% and ~42%, respectively. Interestingly, different studies where CuO NPs were used as an additive obtained similar optimal NP concentrations (0.34 wt.% and 0.5 wt.%) [10,23].…”
Section: Tribological Performance Of Vegetable Nanolubricantsmentioning
confidence: 99%
“…Finally, Danish et al [46] performed milling experiments on Inconel 718 with a sunflower oil reinforced with graphene which reduced surface roughness by 49% and tool wear by 20%. Coconut oil, one of the vegetable lubricants with the highest number of studies in the literature has been reinforced with NPs such as CeO2, Cu, CuO, MoS2, SiO2 and MWNTs [10, 23,36,47,[49][50][51] with COF and wear reductions of up to ~93% and ~42%, respectively. Interestingly, different studies where CuO NPs were used as an additive obtained similar optimal NP concentrations (0.34 wt.% and 0.5 wt.%) [10,23].…”
Section: Tribological Performance Of Vegetable Nanolubricantsmentioning
confidence: 99%
“…The sampling rate was fixed at 60 samples/min for all tribo-tests carried out under the present investigation. The SWR is calculated as shown in Equation ( 1) [20].…”
Section: Tribo-testingmentioning
confidence: 99%
“…The effect of ZrO 2 nanoparticles on the rheological and tribological properties of lubricating oils have been reported by various studies [21][22][23][24][25][26][27]. Philip et al [28] investigated the tribological and thermophysical properties of coconut oil mixed with hybrid nanoparticles (Ce-Zr). It is observed that hybrid nanoparticles improve the tribological properties of oil by rolling and protective film mechanism.…”
Section: Viscosity Index 252mentioning
confidence: 99%